Eplorig Dair Farer’s Kowledge ad Practices of Maure Maageet i Enrekang Regency - Baba, Syahdar; Natsir, Asmuddin; Fatma, Fatma; Idrus, Izdin (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The consequency of the increasing of dairy cattle population in Enrekang is environmentalpollutio fo aue. The ojetie of this eseah as to eploe dai fae’s koledge adpractices of manure management in Enrekang Regency. The design of research was survey with 79respondents from a total of 460 dairy farmers that divided by 65 respondents was small scale (1-3heads each farmer) and 14 respondents was medium scale (more than 3 heads each farmers). Datawere obtained through interview and observations using questionnaire with open and closequestion complementa. Fatos of fae’s koledge ee ethod ad adatage of aueaageet, eooi alue of aue, fae’s eed ad adatage of ogai fetilize. Fatos of fae’s paties ee leaig itesit of a ad dai attle, aue aagementand the use of manure. The data were analyzed with descriptive statistic using frequencydistiutio ad hi suae. Fae’s koledge of aue aageet as the sae eteeediu ad sall sale χ > 5%. The koledge of eooi alue, advantage of organic fertilizerad aue aageet as high hile ethod of aue aageet ad fae’s eed oforganic fertilizer was medium. Cleaning intensity of barn and dairy cattle was high while practice ofmanure handling and manure using was law (rarely).Key Words: Knowledge, Dairy Farmer, Manure